Use of Recombinant Human Stromal Cell–Derived Factor 1α–Loaded Fibrin/Hyaluronic Acid Hydrogel Networks to Achieve Functional Repair of Full‐Thickness Bovine Articular Cartilage Via Homing of Chondrogenic Progenitor Cells. Issue 5 (May 2015) - Yu, Yin; Brouillette, Marc J.; Seol, Dongrim; Zheng, Hongjun; Buckwalter, Joseph A.; Martin, James A.
<x xml:space="preserve">Abstract</x> Objective Articular cartilage damage after joint trauma seldom heals and often leads to osteoarthritis. We previously identified a migratory chondrogenic progenitor cell (CPC) population that responds chemotactically to cell death and rapidly repopulates the injured cartilage matrix, which suggests a potential approach for articular cartilage repair. This study was undertaken to determine whether recombinant human stromal cell–derived factor 1α (rhSDF‐1α), a potent CPC chemoattractant, would improve the quality of cartilage regeneration, hypothesizing that increased recruitment of CPCs by rhSDF‐1α would promote the formation of cartilage matrix upon chondrogenic induction. Methods Full‐thickness bovine chondral defects were filled with hydrogel, composed of fibrin and hyaluronic acid and containing rhSDF‐1α. Cell migration was monitored, followed by chondrogenic induction. Regenerated tissue was evaluated by histology, immunohistochemistry, and scanning electron microscopy. Push‐out tests and unconfined compression tests were performed to assess the strength of tissue integration and the mechanical properties of the regenerated cartilage. Results Use of rhSDF‐1α dramatically improved CPC recruitment to the chondral defects at 12 days. After 6 weeks under chondrogenic conditions, cell morphology, proteoglycan density, and the ultrastructure of the repair tissue were all similar to that found in native cartilage. Compared with empty controls, neocartilage generated in rhSDF‐1α–containing defects showed significantly greater interfacial strength, and acquired mechanical properties comparable to those of native cartilage. Conclusion This study showed that stimulating local CPC recruitment prior to treatment with chondrogenic factors significantly improves the biochemical and mechanical properties of the cartilage tissue formed in chondral defects. This simple approach may be implemented in vivo as a one‐step procedure by staging the release of chemokine and chondrogenic factors from within the hydrogel, which can be achieved using smart drug‐delivery systems.